EVALUASI PROGRAM PEMBINAAN ANAK TERLANTAR DI SASANA PELAYANAN SOSIAL ANAK “KASIH MESRA” DEMAK - Erni Wigianti; Aufarul Marom (Journal of Public Policy and Management Review, 2017)
Abandoned children in Central Java province in 2014 amounted to 66,565, but by 2015 the number has almost doubled to 120,181. Economic reasons and poverty should not be the reason for the placement of children in the institution. Policies that rely on an orphanage system have limited service coverage and are generally less likely to involve parents/families and communities. This study aims to determine the implementation, supporting factors and inhibition of abandoned children's development program in SPSA "Kasih Mesra" Demak and using qualitative descriptive approach with observation data collection techniques, interviews and documentation. Evaluation Model uses CIPP Evaluation Model (Context, Input, Process, Product), from Stufflebeam. Based on the discussion, that Context, beneficiary background is socio-economic condition with the main reason of economic factor and still lack of children assessment includes aspects of needs to family situations and alternative care. Input, the absence of professional social workers, facilities and infrastructure and the existing budget tends to be minimal. Process, children's participation in advising less involved, lack of monitoring and discussion of child development. Product, the number of beneficiaries is sufficient and right on target. Service quality is good and service goal has been reached but not maximal yet. Supporting factors: Support Dinsos Central Java Province and community assistance, Cooperation with parties/external agencies. Inhibiting factors: No professional social worker, limited facilities and infrastructure and beneficiary attitudes in the implementation of coaching activities. Recommendations: Emphasis on child assessment includes aspects of needs of family situations and alternative care. The addition of the implementation of social mental guidance. Recording and evaluation of child development every month. Data collection and submission of list of facilities and infrastructure and the need for human resources continuously and periodically to Dinsos Central Java Province. And the existence of internal training for mentors to increase the competence of social welfare of children.